Experimental methods in heat transfer and fluid mechanics - Han, Je-Chin, 1946-; Wright, Lesley M. (Boca Raton : CRC Press, Taylor & Francis Group, 2020)
Experimental Methods in Heat Transfer and Fluid Mechanics focuses on how to analyze and solve the classic heat transfer and fluid mechanics measurement problems in one book. This work serves the need of graduate students and researchers looking for advanced measurement techniques for thermal, flow, and heat transfer engineering applications. The text focuses on analyzing and solving classic heat transfer and fluid mechanics measurement problems, emphasizing fundamental principles, measurement techniques, data presentation, and uncertainty analysis. Overall, the text builds a strong and practical background for solving complex engineering heat transfer and fluid flow problems. Features Provides students with an understandable introduction to thermal-fluid measurement Covers heat transfer and fluid mechanics measurements from basic to advanced methods Explains and compares various thermal-fluid experimental and measurement techniques Uses a step-by-step approach to explaining key measurement principles Gives measurement procedures that readers can easily follow and apply in the lab
1. Introduction2. Velocity and Flow Rate Measurements3. Temperature and Heat Flux Measurements4. Experimental Planning and Analysis of Results5. Steady-State Heat Transfer Measurement Techniques6. Time Dependent Heat Transfer Measurement Techniques7. Liquid Crystal Thermography Techniques8. Optical Thermography Techniques9. Pressure-Sensitive Paint (PSP) and Temperature-Sensitive Paint (TSP) Techniques10. Mass Transfer Analogy Measurement Techniques11. Flow and Thermal Field Measurement Techniques12. Flow Field Measurements by Particle Image Velocimetry (PIV) Techniques
OCLC-licensed vendor bibliographic record.
Keywords: Heat -- Transmission; Fluid mechanics; SCIENCE / Chemistry / Industrial & Technical; SCIENCE / Mechanics / Dynamics / Thermodynamics; TECHNOLOGY / Engineering / Mechanical